Strategi Pemasaran Peningkatan Penjualan Produk Tenun Troso pada Era Revolusi Industri 4.0 di Kabupaten Jepara - Tri Anisah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The Troso woven fabric industry is a cultural heritage that has developed from generation to generation, with various innovations in the motifs and types of fabrics produced. This study aims to analyze the marketing strategy of the Troso woven fabric industry in Troso Village, Pecangaan District, Jepara Regency, especially in targeting the millennial generation market. This study uses a qualitative-descriptive approach with data collection methods through interviews, observations, and documentation. The data obtained are analyzed using a SWOT analysis to identify internal factors in the form of strengths and weaknesses, as well as external factors in the form of opportunities and threats. The results show that Troso woven fabric craftsmen have implemented a 4P marketing mix (Product, Price, Place, and Promotion) by adjusting the motifs and types of fabrics that consumers are interested in, determining prices according to purchasing power, choosing strategic sales locations, and utilizing social media and marketplaces as promotional tools. The SWOT analysis produces an S-O strategy that emphasizes the use of internal strengths to seize market opportunities, an S-T strategy to deal with threats, a W-O strategy to minimize weaknesses by utilizing opportunities, and a W-T strategy for a defensive strategy. This study recommends that, with the implementation of appropriate strategies, the Troso woven fabric industry can increase sales, expand market reach, and maintain business sustainability in the digital era.